Chromatographic Profile from the Aqueous Extract of Aerial Parts of Centratherum punctatum Cass. - Balasubramanian, Chitra; Pemiah, Brindha (Asian Journal of Biological and Life Sciences, 2015)
Herbal medicine is as primordial as mankind and has appreciably contributed to the health care of the human society. In array to ascertain new bioactive compounds from plant sources which may possibly become new-fangled leads or new drugs, less explored plant extracts should be submitted to chemical screening hyphenated technique such as HPLC and LC-MS. In current study Centratherum punctatum Cass. a traditional drug belonging to the family Asteraceae which grows in arid regions is besieged for metabolite profiling. Some triterpenoids, saponins, flavonoids, isoflavonoids, sesquiterpene and flavonols are identified with the help of computer assisted evaluation of the resulting data. Some of the well-known compounds reported to have great pharmacological importance such as antioxidant and anti-inflammatory property. Such type of research opens the gate for discovery of new compounds initiate in metabolite profiling of plants. Liquid Chromatography - Mass Spectrometry (LC-MS) is proved to be a very useful technique for plant metabolite profiling and allows the identification of a large variety of common plant metabolites in a single chromatogram.
Keywords: Asteraceae; Bioactive compounds; Centratherum punctatum Cass. High pressure thin layer chromatograpy; Liquid chromatography-mass spectrometry (LC-MS) and metabolite profiling